2013
DOI: 10.7763/ijapm.2013.v3.210
|View full text |Cite
|
Sign up to set email alerts
|

First-Principle Studies of Phonons III-N Compound Semiconductors in Wurtzite Structure

Abstract: Abstract-The phonon dispersion relations and density of states of the nitrides BN, AlN, GaN and InN in the wurtzite structure are investigated by using separately the local density approximation (LDA) and the generalized gradient approximation (GGA) within the framework of density functional theory. The results show that the highest optical phonon frequency at the Brillouin zone center decreases, but the phonon band gap increases, with increasing the cation/anion mass ratio. The frequencies calculated with GGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The band gap is related to the mass mismatches of constituent atoms. It has been shown that the band gap increases with increasing the cation/anion mass ratio in binary wurtzite nitrides 28 . The partial DOS of CoSb 3 is also shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The band gap is related to the mass mismatches of constituent atoms. It has been shown that the band gap increases with increasing the cation/anion mass ratio in binary wurtzite nitrides 28 . The partial DOS of CoSb 3 is also shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The spectra of the films as deposited at room temperature, Figure 3(a) exhibits a prominent peak at 470 cm -1 ; while the film as deposited at 200 °C, Figure 3(b) shows a broad peak at 479 cm -1 , which correspond to the transverse-optical (TO) reststrahlen band features of wurtzite structure InN crystal. The obtained E 1 (TO) values are slightly shifted from the reported values 476 cm -1 [19]. The peak shifting as illustrated in Figure 3(a) might probably due to the occurrence of residual stress distortion in crystal unit cell [20].…”
Section: Resultsmentioning
confidence: 64%
“…These obtained values were found to be shifted from the reported values of 476 cm -1 towards lower frequencies. The shifting is probably induced by the residual stress distortion in crystal unit cell [21]. The common strong band located at 521 cm -1 is attributed to the Si(111) substrate, while the two dominant bands correspond to E 2 (high) and A 1 (LO) modes of the wurtzite structure InN can be observed at 487 and 570 cm -1 , respectively.…”
Section: Resultsmentioning
confidence: 97%